2019
DOI: 10.18231/j.ijcap.2019.104
|View full text |Cite
|
Sign up to set email alerts
|

A study on morphological variations of spleen in fetal and adult specimens and it’s clinical significance

Abstract: The spleen is the largest organ of lymphatic system in the human body with distinct circulatory and immunomodulatory functions. Therefore, comprehensive knowledge of splenic anatomical variations and dimensions are essential for early diagnosis, appropriate management and prevention of various infectious diseases and prevention of complications during splenectomy for surgeons. Aim: The aim of the study is to find morphology of spleen in fetus specimens, morphology of spleen in adults and the incidence of varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
2
1
Order By: Relevance
“…We presumed that the irregular contours could be embryonic remnants of fusion borders between adjacent lobules that existed in the earlier stage, which would eventually disappear or remain as notches observed in the adult spleen. It has been reported that the average number of notches in the fetal spleen is approximately three, 21 and usually less than seven in the adult spleen 8,11,36 . Hence, we considered the possibility that the irregular type observed in this study could be abnormal rather than an under‐developing spleen; however, we were not able to acquire enough evidence to confirm our hypothesis from this study.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…We presumed that the irregular contours could be embryonic remnants of fusion borders between adjacent lobules that existed in the earlier stage, which would eventually disappear or remain as notches observed in the adult spleen. It has been reported that the average number of notches in the fetal spleen is approximately three, 21 and usually less than seven in the adult spleen 8,11,36 . Hence, we considered the possibility that the irregular type observed in this study could be abnormal rather than an under‐developing spleen; however, we were not able to acquire enough evidence to confirm our hypothesis from this study.…”
Section: Discussioncontrasting
confidence: 54%
“…It has been reported that the average number of notches in the fetal spleen is approximately three, 21 and usually less than seven in the adult spleen. 8,11,36 Hence, we considered the possibility that the irregular type observed in this study could be abnormal rather than an under-developing spleen; however, we were not able to acquire enough evidence to confirm our hypothesis from this study.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation